The stability of demand for money in the proposed Southern African Monetary Union - Simplice Asongu; Oludele E. Folarin; Nicholas Biekpe (African Governance and Development Institute (AGDI), 2019)
This study investigates the stability of demand for money in the proposed Southern African Monetary Union (SAMU). The study uses annual data for the period 1981 to 2015 from ten countries making-up the Southern African Development Community (SADC). A standard function of demand for money is designed and estimated using a bounds testing approach to co-integration and error-correction modeling. The findings show divergence across countries in the stability of money. This divergence is articulated in terms of differences in cointegration, CUSUM (cumulative sum) and CUSUMSQ (CUSUM squared) tests, short run and long-term determinants and error correction in event of a shock. Policy implications are discussed in the light of the convergence needed for the feasibility of the proposed SAMU. This study extends the debate in scholarly and policy circles on the feasibility of proposed African monetary unions.
Keywords: E41; C22; 330; Stable; demand for money; bounds test